Learning Management In Dirasah Islamiyah At Madrasah Diniyah Assidiqqi Asy-Syuhada - Widodo, Wahyudi (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The purpose of this research is to find out how learning management in Madrasah Diniyah is able to achieve good learning for students. The research method used is qualitative by collecting data through observation, interviews and documentation. The results of this study show that: Learning management at Madrasah Diniyyah Assidiqqi Ash-Syuhada since 2004 has been implemented, as evidenced by the existence of management elements such as learning planning, learning implementation and learning assessment. The most important thing is that the ustad before teaching make a learning plan in advance, even though it is not too detailed like the lesson plan. Then in carrying out learning and ending with the learning assessment process. Thus, the Teaching and Learning Process (PBM) runs smoothly, neatly, and is organized in accordance with clear directions and goals.  In addition, another interesting thing is that pre and post tests are also carried out in learning, even in some activities to invite psychologists, both students and lecturers, especially from the University of Muhammadiyah Malang campus who usually always come every year. So that with this, the learning at Madrasah Diniyah Assidiqqi Ash-Syuhada is getting better and more interesting and has advantages and also high Islam